1997
DOI: 10.1074/jbc.272.10.6208
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Phosphorylation of the Lamin B Receptor by a Serine/Arginine Kinase and p34

Abstract: The lamin B receptor (LBR) is an integral protein of the inner nuclear membrane that is modified at interphase by a nuclear envelope-bound protein kinase. This enzyme (RS kinase) specifically phosphorylates arginine-serine dipeptide motifs located at the NH 2 The nuclear lamina is a filamentous meshwork underlying the inner nuclear membrane (1, 2). In most cells this structure is a heteropolymer of type A and B lamins (3) linked to the inner nuclear membrane through integral membrane proteins. These lamin-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
14

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 45 publications
(58 reference statements)
0
70
0
14
Order By: Relevance
“…However, in the case of the RS protein, LBR, in chicken hepatoma cells, DU249, the level of phosphorylation was similar in I-phase and M-phase cells in vivo (13). In our cell-free system involving Xenopus egg cytosol fractions, the level of phosphorylation of LBR by SRPK was similar in S-phase and M-phase extracts (data not shown).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, in the case of the RS protein, LBR, in chicken hepatoma cells, DU249, the level of phosphorylation was similar in I-phase and M-phase cells in vivo (13). In our cell-free system involving Xenopus egg cytosol fractions, the level of phosphorylation of LBR by SRPK was similar in S-phase and M-phase extracts (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…We demonstrated that the binding of LBR to chromatin is regulated by phosphorylation of LBR in the nucleoplasmic region by cell cycle-specific Xenopus egg cytosol fractions (6). It is also known that LBR is phosphorylated by cdc2 kinase (12,13), SR protein-specific kinase (SRPK) (14), protein kinase A (12), calmodulin-dependent protein kinase II (12), and casein kinase II (12). However, in the cases of all inner nuclear membrane proteins, the protein kinase responsible for the regulation of the binding to chromatin has not yet been identified.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The role of phosphorylation in dismantling the NE and associated heterochromatin is not entirely understood; as exemplified by the LBR-lamin B-chromatin interaction, the binding may be weakened favoring dissociation. 17,56,57 However, in the studied case of chicken LBR, the CDK1 site(s) of mitotic phosphorylation are in dispute: one group 17 identified Thr 188 as the site and suggested that this might destabilize the LBR-lamin B interaction; the other group 57 identified Ser 71 and argued against a weakening of LBR-lamin B binding. More recent studies, 58,59 involving the binding of Xenopus sperm chromatin to LBR-GST beads, present evidence that during S phase the RS protein kinase stimulates LBR-chromatin binding by phosphorylation of one or more serine residues in the RS region (see Fig.…”
Section: The Cell Cycle and Lbrmentioning
confidence: 99%
“…LBR is a polytopic inner nuclear membrane protein consisting of a long, N-terminal domain, seven or eight hydrophobic transmembrane regions, and a C-terminal tail (13). The N-terminal part of the molecule protrudes to the nucleoplasm and contains multiple serine-arginine motifs that are phosphorylated by the SRPK1 and the cdc2 kinases (14,15); the hydrophobic region represents, instead, a (functional) form of sterol reductase and is involved in cholesterol metabolism (16).…”
mentioning
confidence: 99%